Penerapan Sistem Hidroponik sebagai Upaya Mendorong Pertanian Berkelanjutan bagi Warga Kelurahan Nginden Jangkungan - Marreta Coren Tangke; Gyska Indah Harya; Taris Nur Rahma; Faya Pratama Kuncoro Putra; Mazadi Setiawan Yudha (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Land scarcity in urban areas encourages people to look for efficient alternatives to plant cultivation. Hydroponics, as a soil-free cultivation technique, offers a potential solution. This activity aims to carry out socialization and training on hydroponics to improve knowledge and skills in independent plant cultivation that can support household food security in urban communities. The method used was socialization and hands-on practice of making simple hydroponic systems. The results of the socialization and training showed a significant increase in participants' knowledge of the principles of hydroponics. The evaluation percentage is 78% of residents of Nginden Jangkungan sub-district, Sukolilo sub-district, Surabaya city are able to independently apply the Hydroponic system in the yard of each house and can take economic benefits from farming through the hydroponic system, but in the application of this hydroponic system requires high production costs, so that people pay more attention to the use of input allocations used to get more added value. Hydroponics is one of the sustainable agricultural efforts in urban environments that have limited land with the introduction of hydroponic systems, socialization, and application practices in urban areas that have been implemented.